2022
DOI: 10.1007/s00787-022-02077-5
|View full text |Cite
|
Sign up to set email alerts
|

Contextual determinants associated with children’s and adolescents’ mental health care utilization: a systematic review

Abstract: Determinants at the contextual level are important for children’s and adolescents’ mental health care utilization, as this is the level where policy makers and care providers can intervene to improve access to and provision of care. The objective of this review was to summarize the evidence on contextual determinants associated with mental health care utilization in children and adolescents. A systematic literature search in five electronic databases was conducted in August 2021 and retrieved 6439 unique recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 126 publications
0
3
0
1
Order By: Relevance
“…For example, the provision of psychosocial support in schools is influenced by students themselves, teachers, society, parents, and the whole environment. This model was applied to identify the factors that influence the implementation of a structured education program for diabetes 18 and the contextual determinants associated with children's and adolescents' mental health care utilization 6 . Another explanation of the practices' gaps in communication, is that teachers reported low perceived skills in networking with community sources and parents, in the current study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, the provision of psychosocial support in schools is influenced by students themselves, teachers, society, parents, and the whole environment. This model was applied to identify the factors that influence the implementation of a structured education program for diabetes 18 and the contextual determinants associated with children's and adolescents' mental health care utilization 6 . Another explanation of the practices' gaps in communication, is that teachers reported low perceived skills in networking with community sources and parents, in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…5 In addition, several contextual factors could influence the utilization of mental health services among children and adolescents, including their socioeconomic status, the availability of screening programs, stigma, and others. 6,7 One national study in Jordan found that the primary barriers to seeking help among Syrian Refugees and Jordanians include feelings of helplessness, lack of financial means, unawareness and poor recognition of mental health problems, cost of treatment, the need for privacy, and stigma. 5 Thus, implementing interventions in other settings such as school-based interventions is considered a more accessible, acceptable, and sustainable option to reach a larger population of students.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Se considera esencial rescatar una visión radicalmente psicológica de los problemas de salud mental, situando las "raíces" de la conducta en el contexto intersubjetivo, interpersonal y socio-cultural. Resultaría obvio defender que los determinantes sociales (y del entorno escolar, por tanto) tienen un impacto en la salud mental de las personas y en el uso de los servicios socio-sanitarios (Verhoog et al, 2022). Asimismo, la conducta humana obedece más a razones que a causas, y esas razones se tienen que comprender en el contexto biográfico de la persona.…”
Section: La Salud Mental: Cuando Nada De Lo Psicológico Nos Es Ajenounclassified